Driven to Support: Individual- and County-Level Factors Associated With Public Support for Active Transportation Policies. Issue 3 (March 2018) - Cradock, Angie L.; Barrett, Jessica L.; Chriqui, Jamie F.; Evenson, Kelly R.; Goins, Karin Valentine; Gustat, Jeanette; Heinrich, Katie M.; Perry, Cynthia K.; Scanze, Michele; Schmid, Thomas L.; Tabak, Rachel G.; Umstattd Meyer, M. Renee; et al.
Purpose: To assess predictors of stated support for policies promoting physically active transportation. Design: Cross-sectional. Setting: US counties selected on county-level physical activity and obesity health status. Participants: Participants completing random-digit dialed telephone survey (n = 906). Measures: Survey measures assessed stated support for 5 policies to promote physically active transportation, access to active transportation facilities, and time spent in a car. County-level estimates included household car dependence and funding for bicycle–pedestrian projects. Analysis: Multivariable generalized linear mixed models using binary distribution and logit link, accounting for clustering within county. Results: Respondents supported policies for accommodating bicyclists and pedestrians through street improvements (89%), school active transportation programs (75%), employer-funded active commuting incentives (67%), and allocation of public funding (68%) and tax support (56%) for building and maintaining public transit. Residents spending >2 h/d (vs <0.7 hours) in cars were more likely to support street (odds ratio [OR]: 1.87; confidence interval [CI]: 1.09-3.22) and public transit (OR: 1.85; CI: 1.24-2.77) improvements. Residents in counties investing >$1.6 million in bicycle and pedestrian improvements expressed greater support for funding (OR: 1.71; CI: 1.04-2.83) and tax increases (OR: 1.73; CI: 1.08-2.75) for transit improvements compared to those with lower prior investments (<$276 100). Conclusion: Support for policies to enable active transportation is higher where relevant investments in active transportation infrastructure are large (>$1.6 M), public transit is nearby, and respondents drive >2 h/d.